2009
DOI: 10.1002/aic.11892
|View full text |Cite
|
Sign up to set email alerts
|

Particle shape manipulation and optimization in cooling crystallization involving multiple crystal morphological forms

Abstract: A population balance model for predicting the dynamic evolution of crystal shape distribution is further developed to simulate crystallization processes in which multiple crystal morphological forms co-exist and transitions between them can take place. The new model is applied to derive the optimal temperature and supersaturation profiles leading to the desired crystal shape distribution in cooling crystallization. Since tracking an optimum temperature or supersaturation trajectory can be easily implemented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…The shape evolutions of a potash alum crystal demonstrate that the initial 26 faces remain at the end of the simulation, but the shape and size in every face direction are changed. The value of (a 1 -1) 2 + (a 2 -1) 2 approaches zero as the operating condition follows the optimal supersaturation profile [111] which indicates that its morphology does grow to approach the desired morphology. This study demonstrated that the model can be used to derive optimal supersaturation and temperature profiles for a given objective function related to particle shape, hence providing a closed-loop methodology for crystal shape tailoring, which can be easily implemented via a standard feedback or cascade control system using jacket cooling water.…”
Section: Crystal Shape Optimisation and Control Using Mpbmsmentioning
confidence: 99%
See 4 more Smart Citations
“…The shape evolutions of a potash alum crystal demonstrate that the initial 26 faces remain at the end of the simulation, but the shape and size in every face direction are changed. The value of (a 1 -1) 2 + (a 2 -1) 2 approaches zero as the operating condition follows the optimal supersaturation profile [111] which indicates that its morphology does grow to approach the desired morphology. This study demonstrated that the model can be used to derive optimal supersaturation and temperature profiles for a given objective function related to particle shape, hence providing a closed-loop methodology for crystal shape tailoring, which can be easily implemented via a standard feedback or cascade control system using jacket cooling water.…”
Section: Crystal Shape Optimisation and Control Using Mpbmsmentioning
confidence: 99%
“…(3) can be further simplified as (4) It is worth to note that Equations (1-4) can be applied to any crystal systems with the x being crystal internal coordinates and/or other crystal properties. The morphology transformations can be accounted for by varying the number of internal coordinates according to the transformations [111]. Recent studies by Singh et al [112] developed a morphology domain concept which covers all kind of morphologies of a compound, and incorporated it into a MPBM model for automatically detect and model the morphology transformations.…”
Section: Multi-dimensional and Morphological Population Balance Modelsmentioning
confidence: 99%
See 3 more Smart Citations